2021
DOI: 10.1590/0004-282x-anp-2020-0360
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of structural changes in orbitofrontal cortex in relation to medication overuse in migraine patients: a diffusion tensor imaging study

Abstract: Background: Migraine is a prevalent neurological disease that leads to severe headaches. Moreover, it is the commonest among the primary headaches that cause medication overuse headache (MOH). The orbitofrontal cortex (OFC) is one of the structures most associated with medication overuse. Objective: To determine microstructural changes in the OFC among migraine patients who developed MOH, through the diffusion tensor imaging (DTI) technique. Methods: Fifty-eight patients who had been diagnosed with migraine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Mean disease duration ranged from less than three years (Messina et al, 2015 ) to about 34 years (Schmitz et al, 2008 ) among the included articles. Several studies reported mean attack duration, defined as the number of hours each attack lasts (Coppola et al, 2014 , 2020 ; Liu et al, 2013 ), and pain intensity (Coppola et al, 2016a , b ; Coppola et al, 2020 ; Coppola et al, 2014 ; Li et al, 2011 ; Liu et al, 2013 ; Marciszewski & Meylakh, 2019 ; Marciszewski et al, 2018 ; Neeb et al, 2015 ; Russo et al, 2020 ; Tantik Pak et al, 2021 ; Tedeschi et al, 2016 ; Tessitore et al, 2015 ; Yu et al, 2013b ; Zhang et al, 2017 ), based on a pain scale continuum ranging from 0 (no pain) to 10 (severe pain).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean disease duration ranged from less than three years (Messina et al, 2015 ) to about 34 years (Schmitz et al, 2008 ) among the included articles. Several studies reported mean attack duration, defined as the number of hours each attack lasts (Coppola et al, 2014 , 2020 ; Liu et al, 2013 ), and pain intensity (Coppola et al, 2016a , b ; Coppola et al, 2020 ; Coppola et al, 2014 ; Li et al, 2011 ; Liu et al, 2013 ; Marciszewski & Meylakh, 2019 ; Marciszewski et al, 2018 ; Neeb et al, 2015 ; Russo et al, 2020 ; Tantik Pak et al, 2021 ; Tedeschi et al, 2016 ; Tessitore et al, 2015 ; Yu et al, 2013b ; Zhang et al, 2017 ), based on a pain scale continuum ranging from 0 (no pain) to 10 (severe pain).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies investigated microstructural metrics at whole brain level. Nine studies focused on specific pathways as regions of interest: optic radiation (OR) (Rocca et al, 2008 ), corticospinal tract (CST) (Rocca et al, 2008 ), corpus callosum (CC) (Li et al, 2011 ; Rocca et al, 2008 ), red nuclei, PAG, thalami, posterior limbs of IC (PLICs), subcortical WM (Kara et al, 2013 ), thalamus (Coppola et al, 2016a , b ; Coppola et al, 2014 ), cerebellum and brainstem (Qin et al, 2019 ), anterior insula, cingulate gyrus, uncinate fasciculus (Gomez-Beldarrain et al, 2015 ), and orbitofrontal cortex (Tantik Pak et al, 2021 ). Table 2 summarizes the imaging methodologies of the included studies.…”
Section: Resultsmentioning
confidence: 99%